Renewable Energy in Russia: System Analysis of Barriers - A. Ljovkina; M. Brody; E. Karagulyan; A Zakharova; V. Ljovkin (BRICS Law Journal)
Considering the current ecological situation in the modern world, the quality of life depends not so much on a stable energy supply as on an environmentally friendly way of producing and consuming energy, which has turned social and research attention to the opportunities of renewable energy systems (RES). In spite of the vital necessity of transitioning to environmentally friendly energy production, the implementation and development of renewable energy technologies face a range of barriers: socio-cultural, technological, economic, institutional and environmental. To overcome these barriers, the authors of this article use the systems approach to gain deeper understanding of RES interconnection and interdependence. They apply STEEP analysis for classification and qualitative analysis of RES development barriers in Russia. The article proposes the analytical methodology, which reveals system specifications of the national RES development barriers and predicts the chain reaction of overcoming particular barriers. Using this methodology, the authors identify the main socio-cultural roots of RES development barriers in Russia: state control of the development of the energy sector, the political stake in hydrocarbons and the lack of consistent policies on RES development. The authors’ suggested analysis methodology is appropriate for identifying the root problems in energy socio-economic systems and for effective decision-making process in the energy sector.